2004
DOI: 10.1902/jop.2004.75.6.782
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Periodontal Disease and Tooth Loss to Prevalence of Coronary Heart Disease

Abstract: These results suggest that tooth loss and periodontal disease are associated with prevalent CHD, but only when both are present. The weaker relationships between periodontal disease and CHD that have been found among older adults may be due to older adults having fewer teeth. Future longitudinal studies should be designed to ascertain the cause of tooth loss during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 44 publications
8
103
0
6
Order By: Relevance
“…Holmlund [32] showed relevant correlation between the myocardial infarction and the average number of missing teeth in group of 3352 people, who required periodontal treatment and presented themselves with that problem at the dental office. Also Desvarieux [24] and other authors stated the positive correlation between the number of lost teeth and the frequency of atheromatous plaque presence in cervical arteries, detected in ultrasound [25,31].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Holmlund [32] showed relevant correlation between the myocardial infarction and the average number of missing teeth in group of 3352 people, who required periodontal treatment and presented themselves with that problem at the dental office. Also Desvarieux [24] and other authors stated the positive correlation between the number of lost teeth and the frequency of atheromatous plaque presence in cervical arteries, detected in ultrasound [25,31].…”
Section: Discussionmentioning
confidence: 87%
“…In control group of 52 people, the mean number was 4.21 ± 5.62, the differences were statistically relevant. However Elter [31] observed increased risk of cardiovascular disease in patients with significant edentulous area and high Clinical Attachment Level parameters. Holmlund [32] showed relevant correlation between the myocardial infarction and the average number of missing teeth in group of 3352 people, who required periodontal treatment and presented themselves with that problem at the dental office.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous clinical studies have focused on the link between periodontal disease and the morbidity of systemic diseases (Beukers, van der Heijden, van Wijk, & Loos, 2017; Elter, Champagne, Offenbacher, & Beck, 2004; Kim & Amar, 2006). A review article by Slots (2003) concluded that a link between periodontitis—which may harbor a reservoir of human viruses in inflamed gingiva—and systemic disease becomes particularly evident in immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the observation that the strongest predictive effect of periodontal status on kidney disease was found in edentulous individuals (Table 3). Cardiovascular disease prevalence and risk is higher or equivalent in edentulous individuals compared with that in individuals with severe periodontitis in some (35,36) but not all studies (37). In summary, periodontitis predicts the development of both overt nephropathy and ESRD in an American-Indian population with type 2 diabetes.…”
Section: Conclusion -P E R I O D O N T I T I Smentioning
confidence: 99%